Research Progress on Phytopathogenic Fungi and Their Role as Biocontrol Agents - Peng, Yan; Li, Shi J.; Yan, Jun; Tang, Yong; Cheng, Jian P.; Gao, An J.; Yao, Xin; Ruan, Jing J.; Xu, Bing L. (Frontiers in Microbiology, 2021)
Phytopathogenic fungi decrease crop yield and quality and cause huge losses in agricultural production. To prevent the occurrence of crop diseases and insect pests, farmers have to use many synthetic chemical pesticides. The extensive use of these pesticides has resulted in a series of environmental and ecological problems, such as the increase in resistant weed populations, soil compaction, and water pollution, which seriously affect the sustainable development of agriculture. This review discusses the main advances in research on plant-pathogenic fungi in terms of their pathogenic factors such as cell wall-degrading enzymes, toxins, growth regulators, effector proteins, and fungal viruses, as well as their application as biocontrol agents for plant pests, diseases, and weeds. Finally, further studies on plant-pathogenic fungal resources with better biocontrol effects can help find new beneficial microbial resources that can control diseases.